Impact assessment of agriculture and livestock over age, longevity and growth of populations of common toad Rhinella arenarum (Anura: Bufonidae), central area of Argentina - Bionda, Clarisa de Lourdes (2018)
The central area of Argentina has been greatly affected mainly due to urbanization and intensive agriculture (corn, soybean and cattle). Age, longevity and growth were determined in populations of the common toad, Rhinella arenarum, from urban and agricultural sites in the central area of Argentina. Five sites in Rio Cuarto (33º050 52.9500 S - 64º260 02.9900 W, 471 m a.s.l.; Cordoba Province, Argentina) with different degree of anthropic distur- bance were selected to evaluate the impact of urbanization and agriculture on common toad populations as sentinel species. The selected sites were chosen according to intensive to moderate agricultural and livestock activity, low influence of agricultural and an intensive to moderate urban influence. A total of 114 adults (males and females) were sampled. Skeletochronology was used to estimate toad's growth and age, which relies on the analysis of the annual Lines of Arrested Growth or LAGs in bones. Size, age and growth reductions occurrence in intensive agricultural systems could suggest long term impacts on fitness. In addition, intensive urban activity also affects life history of the population of R. arenarum, although to a lesser extent than the agricultural-livestock activity